2020
DOI: 10.7196/samj.2020.v110i8.13466
|View full text |Cite
|
Sign up to set email alerts
|

Nicotine dependence, socioeconomic status, lifestyle behaviours and lifetime quit attempts among adult smokers in South Africa

Abstract: This open-access article is distributed under Creative Commons licence CC-BY-NC 4.0.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
4
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(10 citation statements)
references
References 34 publications
(53 reference statements)
5
4
1
Order By: Relevance
“…In this study, we tried to assess the extent of dependence on nicotine using a Fagerstrom test, as there are not enough studies on this subject in Libya due to the regional conditions and the influence of many social and economic factors. Our findings are consistent with past research [12][13][14][15][16][17]. We noticed an increase in the smoking rate among smokers for physical rather than psychological reasons, previous studies mentioned the same reasons among smokers [18][19][20].In the early morning hours, more than at any other time [21] for reasons mentioned by smokers such as mood, intense desire and a feeling of comfort, it is consistent with what was previously reported [22][23][24].The results showed an increase in the number of cigarettes per day for smokers, which gives an indication of dependence as mentioned in previous studies [25,26].While they were unable to stop during the period of illness, as well as in public places, [27] in accordance with what was mentioned.…”
Section: Resultssupporting
confidence: 94%
“…In this study, we tried to assess the extent of dependence on nicotine using a Fagerstrom test, as there are not enough studies on this subject in Libya due to the regional conditions and the influence of many social and economic factors. Our findings are consistent with past research [12][13][14][15][16][17]. We noticed an increase in the smoking rate among smokers for physical rather than psychological reasons, previous studies mentioned the same reasons among smokers [18][19][20].In the early morning hours, more than at any other time [21] for reasons mentioned by smokers such as mood, intense desire and a feeling of comfort, it is consistent with what was previously reported [22][23][24].The results showed an increase in the number of cigarettes per day for smokers, which gives an indication of dependence as mentioned in previous studies [25,26].While they were unable to stop during the period of illness, as well as in public places, [27] in accordance with what was mentioned.…”
Section: Resultssupporting
confidence: 94%
“…alcohol) 24 , which makes nicotine dependence more severe, promoting continued smoking and fewer quit attempts in this population group 25 . The CPD patterns in this study highlight a few issues -they confirm previous analyses that most smokers in South Africa are 'light smokers' and may therefore be motivated to quit, if offered brief advice 26 . Also the association between higher number of smoked CPD and higher socioeconomic status (SES), reflected in this study as having attained greater than high school education and living in urban areas, may suggest higher level of dependence among those of higher SES, which is consistent with what was recently reported in South Africa 26 .…”
Section: Discussionsupporting
confidence: 82%
“…Results of the present study also showed that the amount of smoking, smoking behavioral dependence, and less physical activity were factors likely to lead to greater levels of nicotine dependence. Agreement between results of prior studies supports the assumption that nicotine acts in the brain through neuronal nicotinic acetylcholine receptors (nAChRs), which cause cigarette cravings and withdrawal symptoms, ultimately leading to restarting smoking (Ayo‐Yusuf & Omole, 2020; Scheidl et al, 2021). Previous studies have also found that physical activity or exercise can alleviate the negative effects of withdrawal symptoms and decrease smoking behavior (Klinsophon et al, 2020; Soreca et al, 2020).…”
Section: Discussionmentioning
confidence: 61%
“…Based on this framework, we assumed that nicotine dependence is affected by patients’ disease characteristics, personal smoking behaviors, physical activity, physical and social–emotional function, social support, and psychological distress. Previous studies of nicotine dependence among patients have indicated that biological factors include higher behavioral dependence (Scheidl et al, 2021), less physical activity (Ayo‐Yusuf & Omole, 2020), and reduced physical function (Fidai et al, 2019). Psychological factors include lower social–emotional function (Buu et al, 2021), and greater degrees of depression (Buu et al, 2021).…”
Section: Introductionmentioning
confidence: 99%